Viral-Induced Mortality of Prokaryotes in a Tropical Monsoonal Estuary - Jasna, Vijayan; Parvathi, Ammini; Pradeep Ram, Angia Sriram; Balachandran, Kizhekkapat K.; Madhu, Nikathil V.; Nair, Maheswari; Jyothibabu, Retnamma; Jayalakshmy, K. Veeraraghava; Revichandran, Chenicherry; Sime-Ngando, Télesphore (Frontiers in Microbiology, 2017)
Viruses are recognized as the most abundant and dynamic biological entities in the marine and estuarine environment. However, studies on the dynamics and activity of viruses in transient estuarine systems are limited. This study examines temporal and spatial variations in viral abundance (VA) and viral activity across the salinity gradient in a monsoon-driven tropical estuarine system (Cochin estuary, CE) along the southwest coast of India. Water samples were collected from five stations (with different hydrological settings) every 3 h for 24 h period during two distinct seasons, namely pre-monsoon (PRM, dry season) and monsoon (MON, wet season). Time series measurements were made for a spring and neap tidal cycle for each season at all the stations. The results showed marked spatial and seasonal variability with relatively low diel and tidal variations in VA and lytic activity. Viral activity was found to be distinct in five stations studied with the maximum activity in the mesohaline regions (salinity < 20) of the estuary. This region was characterized by high VA, lytic infection and viral production, accompanied by low bacterial growth efficiency and high bacterial respiration. Based on viral lytic production, lytic viruses were found to be responsible for the release of ca. 72.9 ±58.5 µg C L-1d-1of bacterial carbon. The contribution of the viral shunt to the dissolved organic carbon pool was higher during the dry season (PRM) than MON. Statistical analysis confirmed a significant association of viruses with the host availability and salinity. This work demonstrates the spatiotemporal distribution of viruses in a tropical estuarine ecosystem and highlights their role in microbial mortality across different salinity gradients.This study forms the first report on viral processes from a monsoon-driven tropical estuarine ecosystem.